Odpowiedzi

Najlepsza Odpowiedź!
2009-12-29T19:16:08+01:00
( -2 - 2x) (-4 + 3x)=8-6x +8x-6x^2=-6x^2+2x +8
( -6 - 3x) ( - 5 - 8x)=30+48x+15x+24x^2=24x^2+63x+30


(x + 2) (3+x) = x(x+1) + 2
3x+x^2+6+2x=x^2+x+2
3x-x=2-6
2x=4
x=2

-(x-3) (2x+1) = -2(6+ x²)
-2x^2+x-6x-3=-12-2x^2
-2x^2-5x-3=-12-2x^2
-5x=15
x=-3
1 5 1
2009-12-29T19:22:51+01:00
(-2 - 2x) (-4 + 3x)=8-6x+8x-6x(kwadrat)=8+2x-6x(kwadrat)
( -6 - 3x) ( - 5 - 8x)= 30 +40x + 15x + 24x(kwadrat) = 30 + 55x + 24x(kwadrat)


(x + 2) (3+x) = x(x+1) + 2
3x + x(kwadrat) +6 +2x = x(kwadrat) + x + 2
5x + x(kwadrat) + 6 = x(kwadrat) + x + 2
5x - x + x(kwadrat) - x(kwadrat) = 2 - 6
4x = -4 /:4
x = (-1)

-(x-3) (2x+1) = -2(6+ x²)
- (2x(kwadrat) + x - 6x - 3) = -12 - 2x(kwadrat)
-2x(kwadrat) - x + 6x + 3 = -12 - 2x(kwadrat)
-2x(kwadrat) + 5x + 3 =-12 - 2x(kwadrat)
-2x(kwadrat) + 2x(kwadrat) + 5x = -12 + 3
5x = -9 /:5
x = 1 cała i cztery piąte


mam nadzieję,że pomogłam
1 5 1
2009-12-29T19:28:47+01:00
( -2 - 2x) (-4 + 3x)=8-6x+8x-6x^2=8+2x-6x^2=

( -6 - 3x) ( - 5 - 8x)= 30+48x+15x+24x^2=24x^2+63x+30

(x + 2) (3+x) = x(x+1) + 2
3x+x^2+6+2x=x^2+x+2
4x=-4
x=-1

-(x-3) (2x+1) = -2(6+ x²)
-(2x^2+x-6x-3)=-12-2x^2
-x+6x+3=-12
5x=-15
x=-3
2 5 2